Crustal flow and fluids affected the 2021 M7.4 Maduo earthquake in Northeast Tibet. (March 2022) - Yang, Ziqiang; Zhao, Dapeng; Dong, Yunpeng; Cheng, Bin
Graphical abstract: Highlights: Fluids exist in the Maduo source zone and affected the rupture nucleation. Depth-varying seismic anisotropy occurs and reflects lower-crustal flow. The ductile flow in the mid-lower crust affected the seismotectonics. Abstract: We present detailed 3-D tomographic images of P and S wave velocity (Vp, Vs), Poisson's ratio (ν) and Vp azimuthal anisotropy of the crust and uppermost mantle beneath the source area of the 21 May 2021 Maduo earthquake (M 7.4) in the NE Tibetan plateau. The images are obtained by inverting a large number of P and S wave arrival-time data of 11, 235 local earthquakes and Maduo aftershocks recorded at 67 seismic stations. Our results show that the 2021 Maduo mainshock occurred in a low-Vs and high-ν anomaly, probably reflecting crustal fluids that affected the rupture nucleation. Our Vp anisotropy results show that at 40 km depth under the southern part of the study region, the fast-velocity direction (FVD) is NW-SE, which is mainly controlled by the India-Eurasia collision. At 60 km depth under the study region and at 40 km depth under the northern part of the region, the FVDs are NE-SW to N-S, reflecting lower crustal flow. The FVDs are roughly E-W at 60 km depth beneath the Qilian mountain range, which reflect the lower crustal flow that is blocked by a rigid terrane in the north. The lower crustal flow may lead to intra-crustal and crust-mantle decoupling and affect seismotectonics in NE Tibet.